PENINGKATAN DIGITAL SKILL BAGI PENGUSAHA UMKM - Wati, Lela Nurlaela; Mulyanti, Rita Yuni; Soma, A. Mukti; Supriatiningsih, Supriatiningsih; Darwis, Hidayat (Asosiasi Dosen Muda Indonesia, 2023)
Micro, small and medium enterprises are required to continue to move quickly to keep up with changes and to be able to adapt to modern and dynamic environmental conditions. Business innovation by utilizing the development of digital technology, has a major influence on the perspective of MSMEs in running their business. It is very important for SMEs to optimize the use of increasingly sophisticated technology and the use of social media as a means of social networking in marketing their products. Therefore the community service team from STIE Muhammadiyah Jakarta conducts training to increase the digital skills of MSME entrepreneurs in collaboration with the Telkom Community Development Center Jakarta, with the aim of providing explanations and understanding for all MSME participants regarding the use of digital technology, Providing tips on how to deal with problems in this era 4.0, provides an understanding of the use of copy writing to increase sales and provides tips on how to establish as many social networks as possible. MSMEs understand the importance of using digital so they can get used to processing today's technology, know tips on using digital in dealing with problems in the 4.0 era, know the use of copy writing so that sales increase, communication networks will be established between each other and the community.